Enforcement of Zina Laws in Islamic Law and Positive Law: Criticism of the Judge's Decision and Offer of Solutions - Musyafa,; Yassir, Muhammad; Fachri Zain, Bayu Rizky (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2024)
The enforcement of zina law in Islamic law and positive law in Indonesia shows significant differences in the definition, application of sanctions, and legal process. This difference creates a misalignment between society's expectation of a strict application of sharia norms and the more lenient rules of positive law. In Islamic law, adultery is a serious offense with strict sanctions such as stoning or flogging, while Indonesian positive law only provides minor criminal penalties for perpetrators who are bound by marriage, and often does not provide the deterrent effect expected by society. This research aims to criticize the judges' decisions in handling adultery cases and propose solutions through harmonization of Islamic law and positive law, based on the principle of Maqasid al-Syariah. This research approach uses qualitative research, reviewing literature with literature studies. Normative and comparative analysis is conducted to understand the discrepancies and their implications for the protection of the rights of children out of wedlock, which in Islamic law is often not recognized as the status of the biological father, but is recognized in positive law. The results show that harmonization between the two legal systems is necessary to bridge this discrepancy and provide substantive justice for children of adultery. The implementation of Maqasid al-Syariah is expected to protect children's rights while strengthening sanctions against perpetrators, thus meeting the expectations of social justice without ignoring the basic values in Islamic law.